Innovative CMOS-fabricated dielectrophoretic chip: application of 3D TiN nano-electrode arrays with adjustable electrode spacing in sperm capture - Liao, I-Hsuan; Shiau, Jeng-Huei; Chou, Kuan-Ru; Lien, Chun-Lung; Cheng, Chao-Min (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction: Dielectrophoresis has been considered an effective method for particle sorting, and scientists have used it to manipulate sperms. However, due to the limitations of the chip fabrication, the conventional dielectrophoresis chip would face several issues such as low throughput, Joule heating, and insufficient dielectrophoretic force in terms of practical applications. To overcome these limitations, we have developed 3D TiN nano-electrode arrays through employing CMOS technology. The electrodes were scaled down to the nanometer scale, and an insulating layer was used to isolate large areas of wiring, thereby reducing the impact of Joule heating on sperms while simultaneously enhancing the electric field strength. Compared to conventional micro-electrodes, the exposed area of micro-electrodes per unit area has been approximately 840 times larger than that of our nano-electrodes, while the electric field strength of nanoelectrodes has been about 5 times higher than that of micro-electrodes.Methods: Our experimental results showed that variations in either applied voltages or applied frequencies with the capacity of adjustable electrode spacing significantly influenced sperm capture efficiency.Results and discussion: Notably, the sperm capture “net” with different sizes could be created by adjusting electrode spacing, providing a variety of sperm capture net configurations that could be used to examine sperm capture efficiency. The optimal sperm capture condition would be a capture space of 70 µm, an applied voltage of 20 Vpp, and an applied frequency of 3 MHz. Under this condition, the sperm capture efficiency could reach 59.98% ± 0.93%, demonstrating a promising capture efficiency for motile sperm. In addition, the throughput of single dielectrophoresis chip could reach 6 mL/h, and multiple chips could be operated simultaneously according to the demand.